Correction to “Sparse Array Mutual Coupling Reduction” [Feb 23 201-216] - C. Larmour; N. Buchanan; V. Fusco; M. Ali Babar Abbasi (IEEE Open Journal of Antennas and Propagation)
In the paper [1], Fig. 1 (c), captioned “Sparse array designs for (c) Compressive sensing direction-of-arrival estimation,” was incorrectly included in the final version. This image has not received the appropriate copyright approval for reuse and therefore should be removed as shown in the updated Fig. 1. The corresponding reference as shown in [2] should also be removed from the reference list.